INVESTMENT RISK PROFILE, INVESTMENT BEHAVIOR AND SUBJECTIVE WELL-BEING OF DUAL EARNER FAMILY: Profil Risiko Investasi, Perilaku Investasi Dan Kesejahteraan Subjektif Keluarga Berpenghasilan Ganda - Sari, Nova Nurmala; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Dual-income families are currently a global phenomenon that occurs due to the increasing economic demands on families. Economic demands on families. Dual-income families have a source of income from two sources of income, namely, the wife and husband. Dual-income families have the opportunity to allocate income to invest so that in the future, financial problems do not arise due to a lack of awareness in managing income, which can affect the subjective well-being of the family. This study aims to determine the effect of investment risk profile and investment behavior on dual-income family welfare. On dual-income family welfare. This study used a cross-sectional research design located in Depok City. A total of 100 working wives involved in this study were selected purposively. Data were collected using an online questionnaire. Data were analyzed descriptively, and correlation and regression tests were conducted using the SPSS version 25.0 application. The results showed that there is a relationship between education, wife's income, husband's education, investment behavior, and subjective well-being with investment risk profile. The results also show that there is a relationship between the wife's education, the husband's income, and subjective well-being with investment behavior. The regression test results show that investment behavior has a significant positive effect on the investment risk profile.